Main directions and perspectives of rice breeding for conditions of Ukraine - Р. А. Вожегова; В. З. Лисенко (Plant Varieties Studying and Protection)
The directions and results of rice breeding work in Ukraine are accounted in article. Parameters of rice variety for conditions of Ukraine are represented. The brief characteristic of the best varieties created in Institute of rice of UAAS per last years is given.